KOMUNIKASI PEMBANGUNAN IBU KOTA NUSANTARA (IKN) DAN ISU LINGKUNGAN DALAM PERSPEKTIF ETIS PEMBANGUNAN - Muhamad Irfan; Mite Setiansah; Nana Sutikna (Jurnal Ranah Komunikasi, 2022)
The government has announced the transfer of the capital city from DKI Jakarta to the Archipelago Capital (IKN) in Kalimantan. The purpose of this research is to analyze development communication carried out by the government towards the development of IKN regarding environmental issues in an ethical perspective of development. Research using qualitative methods with a descriptive approach. The research data used is secondary data from the results of the literature review. Research shows that there is community rejection based on environmental issues due to the government's lack of effective development communication.